2017
DOI: 10.1590/2359-3997000000252
|View full text |Cite
|
Sign up to set email alerts
|

Related quality of life questionnaire specific to dysthyroid ophthalmopathy evaluated in a population of patients with Graves’ disease

Abstract: Objective: The aim of this study was to measure quality of life (QOL) impairment in individuals currently suffering from Graves' ophthalmopathy (GO) and to determine the correlation of GO-specific QOL scores with disease severity and activity. Subjects and methods: Seventy three GO-specific QOL surveys were prospectively analysed and compared with GO status. The GO-specific QOL survey was translated into Spanish and applied to Argentine patients with Graves' disease (GD). Results were compared with presence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
4
9
1
Order By: Relevance
“…Therefore, ocular pain is likely a significant driver of QOL decrement in patients with TED. These findings are in agreement with prior studies which demonstrated that increasing disease activity [11,21,22,24,25] and ocular pain [10,11] significantly impair patient QOL. It should be noted that smaller, earlier published studies did not find a significant correlation between patient-perceived QOL and disease activity [20,29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, ocular pain is likely a significant driver of QOL decrement in patients with TED. These findings are in agreement with prior studies which demonstrated that increasing disease activity [11,21,22,24,25] and ocular pain [10,11] significantly impair patient QOL. It should be noted that smaller, earlier published studies did not find a significant correlation between patient-perceived QOL and disease activity [20,29].…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that overall disease severity, rather than any one severity measure, drive physician-perceived QOL impact in patients with TED. This conclusion is supported by patient-perceived QOL studies that show an increased QOL impact in patients with more severe disease [21][22][23][24][25]. On the other hand, eye muscle involvement, and the resulting sequelae (e.g., strabismus and diplopia), have been previously shown to specifically negatively influence QOL in TED patients [10-12, 22, 24].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results showed worse STED-QoL scores in patients with more severe disease as well as in those who had undergone surgery, although our results were unadjusted for confounders, such as age, sex, and sociodemographic and clinical factors. Similar findings have been reported by Delfino et al, 32 who used the Spanish translated version of the Go-QOL questionnaire in a cohort of 71 patients (56 GO patients and 15 controls) and found lower QOL scores in patients with more severe GO.…”
Section: Discussionsupporting
confidence: 89%
“…Multivariate analysis in our study showed EOM involvement, proptosis, and severity of eye disease predicted the visual functioning scores, however, only severity of eye disease predicted appearance scores and similar results were seen in German, Korean, and Spanish study. [ 8 21 22 ] Significant ceiling effects (21.4%) were seen in the visual functioning subscale, which suggests that patients had a maximum response to this scale. Similar ceiling effects were also seen in the German study (27%).…”
Section: Discussionmentioning
confidence: 99%